A case study on the source apportionment of indoor air quality (IAQ) in selected kindergarten using cluster analysis - Mohd Sidek, Salmi Syuhada (2023)
Indoor air quality is an important concern for kindergarteners. There is scientific evidence to suggest that children are more likely to develop respiratory problems if they spend time indoors while pollutants such as organic and inorganic chemicals can be harmful. The study's primary goal will be to determine the trend and source of pollutants inside kindergartens using descriptive analysis and cluster analysis. Air temperature (T), relative humidity (RH), air movement (AM), carbon dioxide (CO2), formaldehyde (HCHO) and particulate matter (PM) are the monitored parameters. Monitoring was carried out in the kindergarten for three consecutive days started from 8 a.m. to 12 p.m. According to this, indoor carbon dioxide readings were higher at 8 a.m. when parents drove to kindergarten to drop off their children without turning off the engine. In addition to this, the PM10 reading at 10am was high but still within the standard range according to ICOP IAQ 2010. The findings highlight the importance of indoor air quality improvement measures for kindergarten buildings in different environments, which can be used to improve indoor air quality in kindergarten environments.